2021
DOI: 10.1111/ijfs.15082
|View full text |Cite
|
Sign up to set email alerts
|

Technological and functional properties of reduced‐salt pork batter incorporated with soy protein isolate after pressure treatment

Abstract: Summary To investigate the effects of different pressures (0.1–400 MPa), the techno‐functional properties, water distribution and mobility of reduced‐salt pork batters (1% NaCl) supplemented with soy protein isolate (SPI, 2%) were examined. Compared with the batters treated at 0.1 MPa, those treated at 100–300 MPa showed significantly increased the cooking yield, hardness, springiness, cohesiveness, chewiness, and G′ values of gel and reduced the initial relaxation times of T2b, T21 and T22, as observed from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…A possible reason is that changes in protein conformation and molecular interactions, such as electrostatic bonds, hydrogen bonds, and hydrophobic interactions, resulted from high-pressure processing, which could then increase/decrease the technological and functional properties of muscle proteins ( Li et al, 2020a ). A similar result was reported by Li, Sukmanov, Kang and Ma (2021b) , where the L* value of cooked batter treated with high pressure before heating significantly increased, and the a* and b* values significantly decreased when the pressure exceeded 200 MPa. Yang et al (2016) also found that the colour of reduced-fat sausage treated at 200 MPa was lighter than that treated at 0.1 MPa.…”
Section: Resultssupporting
confidence: 88%
“…A possible reason is that changes in protein conformation and molecular interactions, such as electrostatic bonds, hydrogen bonds, and hydrophobic interactions, resulted from high-pressure processing, which could then increase/decrease the technological and functional properties of muscle proteins ( Li et al, 2020a ). A similar result was reported by Li, Sukmanov, Kang and Ma (2021b) , where the L* value of cooked batter treated with high pressure before heating significantly increased, and the a* and b* values significantly decreased when the pressure exceeded 200 MPa. Yang et al (2016) also found that the colour of reduced-fat sausage treated at 200 MPa was lighter than that treated at 0.1 MPa.…”
Section: Resultssupporting
confidence: 88%
“…Therefore, the solubility of myofibrillar proteins and the cooking yield increased by increasing the NaCl content from 1 to 2% (Paula et al, 2019;Kang et al, 2021b). Moreover, SPI has excellent gelling properties, good water-and fatholding capacity, and structuring behaviour (Berghout, Boom & Goot, 2015;Li et al, 2021), which could improve the cooking yield of frankfurters at a NaCl content of 1%, since the N2 and N1-S3 cooking yields were not significantly different. Bertram et al (2008) reported that SPI increased the stability of pork batters and improved the water-and fat-holding capacity during cooking.…”
Section: Cooking Yieldmentioning
confidence: 99%
“…Therein, added non‐meat proteins to pork batter can be an effective method to amplify gel properties (Gao et al ., 2015; Sha & Xiong, 2020). Our previous studies have found that the addition of soy protein isolate could improve the emulsion stability and gel properties of low‐salt pork batter and pork myofibrillar protein treated at 200 MPa (Li et al ., 2020, 2021a, 2021b). As the main component of soy protein isolate, soy 11S globulin shows excellent emulsification properties (Perrechil et al ., 2015) and gelation ability (Tarone et al ., 2013; Kang et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%